Application of red pigment producing edible fungi for development of a novel type of functional cheese. Issue 10 (21st September 2018) - Kumura, Haruto; Ohtsuyama, Takeru; Matsusaki, Yoh‐hey; Taitoh, Miho; Koyanagi, Haruka; Kobayashi, Ken; Hayakawa, Toru; Wakamatsu, Jun‐ichi; Ishizuka, Satoshi
Abstract : To develop a novel type of functional cheese, nine strains of edible fungi, Monascus sp. were cultured on whey protein‐based solid medium and screened in terms of secondary metabolite production including red pigments, lovastatin, and citrinin. The amount of these metabolites in culture products depended not only on the strain, but also on the pH and temperature environment. The strain of M .  ruber NBRC 32318 was selected because it produced red pigments and lovastatin with negligible amount of citrinin. After incubation at 25°C for 10 days with initial pH condition of 4.0, the culture products were mixed with cheese curds, followed by ripening for 3 months at 11.5°C. Higher level of water‐soluble nitrogen was recognized in the culture products containing cheese compared to control cheese. Practical applications: For cheese making, diverse microorganisms have been used. However, there have been limited trials on the development of dairy products using red pigment producing Monascus species used for fermented rice in the Eastern Asia for more than 1, 000 years. Using whey protein base solid substrate, we selected suitable Monascus strain and defined the culture condition that provided nephrotoxin citrinin‐free and functional metabolite of lovastatin‐containing culture products, which were mixed with fresh cheese curds for ripening. In the resulting red mold cheese, proteolysis was accelerated with no bitter flavor and rancid. Although further assessments concerning health benefits by animal studies and cheese quality by sensory evaluation are necessary to be commercialized as a novel type of functional cheese, this study provides fundamental information regarding screening of suitable strains with its appropriate culture condition on whey protein solid substrate, focusing on biotechnological, and chemical respects to ensure food safety.